PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PRODUK GADAI EMAS (Studi kasus Bank Syariah Mandiri Cabang Medan Marelan) - Lukman Hakim Siregar (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2018)
As Generally Society when need the fund and tobe as valuables, people as guarantee to owners of funds that is pawn shops as their destination as formal or non formal without use the rule of sharia systems, not as sharia banking to services of pledge sharia rule’s. Bank as a pawn has two factors which are interconnected to rich function from bank as depositors for the people. Branch of Bank Syariah Mandiri Marelan offer the product to society as a one of product from pawn shops sharia banking where the customers growth. That is the services done by one of the largest sharia banking in Indonesia must have able to answer satisfaction from customers.